The answer here is that x = 6 and y = 5. Here is how you can find this:

The thing to do here is to take the value that you have been given for x in the second equation and substitute it into the first equation. So then you have

3 (2y - 4) - 2y = 8

6y - 12 - 2y = 8

4y = 20

y = 5

Now you take this value of y and substitute it back in to the second equation to find x.

x = 2 (5) - 4

x = 10 - 4

x = 6

3x-2y=8...(1)

x=2y-4

Subtract 2y

==> x-2y=-4.....(1)

Subtract (1) from (2)

==> 2x=12 ==> x=6

To calculate y, we will use either equation (1) or (2)

x-2y=-4

Substitute with x=6

==> 6-2y=-4

Subtract 6 from both sides:

==> -2y=-10

Divide by -2:

==> y=5

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now